2017
DOI: 10.4274/balkanmedj.2015.1616
|View full text |Cite
|
Sign up to set email alerts
|

Normal and Tumour Tissue mRNA Expressions of Telomerase Complex Genes in Several Types of Cancer

Abstract: Aims:To investigate the changes in mRNA expression levels of telomerase-related significant proteins in several types of cancer.Methods:Human telomerase reverse transcriptase, pontin, reptin and dyskerin expressions were measured in normal and tumour tissues obtained from 26 patients with colorectal, breast and gastric cancers, using the real-time reverse transcriptase-polymerase chain reaction method.Results:For all patients, no significant difference was found in mRNA expressions of human telomerase reverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Caliskan et al [5] found that telomerase activity regulates the expression of human telomerase reverse transcriptase (hTERT) in GC cells, and proposed that inhibiting telomerase activity may be a potential Another study evaluated the telomerase activity of BGC-823 human GC cells using the PCR-TRAP method and found that gambogic acid (GA) can inhibit telomerase activity by inhibiting Akt phosphorylation and reducing hTERT expression. Duan et al [6] confirmed that piperonamide (PL) exerts anti-cancer effects by inhibiting telomerase activity and cell proliferation.…”
Section: Inhibition Of Telomerase Activitymentioning
confidence: 99%
“…Caliskan et al [5] found that telomerase activity regulates the expression of human telomerase reverse transcriptase (hTERT) in GC cells, and proposed that inhibiting telomerase activity may be a potential Another study evaluated the telomerase activity of BGC-823 human GC cells using the PCR-TRAP method and found that gambogic acid (GA) can inhibit telomerase activity by inhibiting Akt phosphorylation and reducing hTERT expression. Duan et al [6] confirmed that piperonamide (PL) exerts anti-cancer effects by inhibiting telomerase activity and cell proliferation.…”
Section: Inhibition Of Telomerase Activitymentioning
confidence: 99%
“…Çalışkan et al17 found that telomerase activity regulates the expression of human telomerase reverse transcriptase (hTERT) in gastric cancer cells, and suggested that inhibiting telomerase activity may be a potential anti-cancer therapeutic mechanism. Another study18 utilized the PCR-TRAP method to evaluate telomerase activity in BGC-823 human gastric carcinoma cells, and found that gambogic acid (GA) can inhibit telomerase activity by inhibiting the phosphorylation of Akt and reducing the expression of hTERT.…”
Section: Inhibition Of Proliferation Of Gastric Cancer Cellsmentioning
confidence: 99%